TI_GERICHTE 52.2023.431 vom 10. April 2024 , Commessa pubblica. Conformità dell'offerta (prodotto equivalente) - TI Tribunale d'appello (2024)
Commessa pubblica. Conformità dell'offerta (prodotto equivalente)